Factors Influencing Surgical Outcome of Patients with Traumatic Acute Subdural Hematoma (Bangladesh Journal of Neurosurgery, 2024)
Background: Traumatic acute subdural hematoma (ASDH) is a catastrophic   devastating component of brain injury in neurosurgical arena. Due to its significant   mortality rate, potential for functional disability and disastrous consequence of   complications, it is considered as a challenge for neurosurgeons worldwide.   Consequently, precise recognition of predictive outcome factors is crucial for appropriate   neurosurgical management and prognostication for patients with traumatic ASDH.   Aims: The study aimed to determine the demographic, clinical, radiological and   therapeutic factors associated with the surgical outcomes in patients with traumatic   acute subdural hematoma (ASDH) who managed surgically in the Neurosurgery   Department at a tertiary level hospital in Bangladesh.   Materials and Methods: This prospective observational study included 40   radiologically diagnosed cases of traumatic ASDH age more than 18 years who were   admitted and operated in the Department of Neurosurgery of Chittagong Medical   College Hospital from May 2022 to April 2023. Data regarding demographic, clinical,   radiographic, surgical procedure and findings were recorded. Three months mortality   rate with clinical outcome was assessed by Glasgow Outcome Scale (GOS) score and   analyzed. The outcome was divided into favorable outcomes (GOS score >3) and   unfavorable outcomes (GOS score d”3).   Results: The median age of the patients was 45 years (range: 19-82 years), and   there was a male predominance (82.5%) with a male to female ratio of 4.7:1. Road   traffic accident (RTA) was the most common cause of trauma (65%), followed by fall   from height (15%), and physical assault (12.5%). Craniotomy was done in 16 (40%)   patients and other 24 (60%) patients had decompressive craniectomy. Overall, 21   (52.5%) patients had good outcome and other 19 (47.5%) had poor outcome, and three   months mortality rate was 42.5%. Regression analysis revealed that, increasing age   [Odds ratio (OR): 1.12, 95% Confidence interval CI: 1.02-1.22. p=0.014], preoperative   GCS of d”8 (OR: 13.98, 95% CI:1.22-160.00, p=0.034), and presence of Anisocoria   with non-reacting pupil (OR; 17.99, 95% CI: 1.32-244.08, p=0.030) were   independently associated with poor outcome.   Conclusions: This study identified higher age, preoperative low GCS score and   pupillary abnormality as the independent predictors for 3-months poor outcome in   patients who underwent surgical treatment for traumatic ASDH  Bang. J Neurosurgery 2024; 13(2): 140-148